Pemanfataan Aplikasi Canva Sebagai Media Pembelajaran Masa Kini dalam Kurikulum Merdeka - Aisyah Ika Shauman Ninta; Muhammad Sofian Hadi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The era of digitalization is growing rapidly, including in the field of education. Educators and students need technology or platforms that support distance learning activities and still have good interaction, so that classes remain not bored or fun and productive. One platform that can answer these challenges is the Canva application. Canva has one of the special services or programs designed for education, namely Canva for Education. This service is designed for educators and students to continue to get a creative, innovative, collaborative and fun learning experience in line with the independent curriculum.The method used in this study is a development research method with a descriptive quantitative approach. This study aims to describe the use of the Canva for Education application by educators as a creative, innovative and collaborative learning medium for students in the current era